Blended Learning Syarah: Bagaimana Penerapan dan Persepsi Mahasiswa - Puji Astuti; Febrian Febrian (Jurnal Gantang, 2019)
This study aims to see how the implementation and students’ perceptions of e-learning type blended learning in Mathematics Capita Selecta course. The e-learning in this study utilized the Syarah portal, an online learning application developed by Universitas Maritim Raja Ali Haji (UMRAH) responding to the 4.0 era. This online learning using Syarah was the first time applied to research subjects, namely 35 students of Mathematics Capita Selecta Course year 2019. The data was collected from the results of the researchers' observations during the learning process and students’ responses to the questionnaire. The data were analyzed qualitatively to describe how the implementation of e-learning and how students’ perceptions about e-learning Syarah in supporting them to learn. The results of the analysis show that the Syarah system and students are ready for the implementation of online learning. Students’ confusion only occurs at the initial meeting of each type of e-learning activities designed by the researcher. Hereinafter, students could carry out learning well, even independently, but with clearly stated instructions. In addition, students were actively involved during the e-learning process. It also reveals that students felt more open to engaging in e-learning activities than when they were in class. In general, students gave positive responses to the use of Syarah in supporting blended learning.